Relocation from Esplanade to Bhuleshwar - Mumbai Archive Project Team (Jio Institute, 2024)
A Koli fisherwoman installed the old shrine to Mumba Devi on the Esplanade, just outside the British Fort, according to the popular narrative. In 1737, land was provided by the British East India Company for the relocation of the temple to Bhuleshwar.